Comparison of the Angular Compartment of Hip Flexion Before and After Training in 11 to 12-Year-old Soccer Players. - Jair Burboa G; Mauricio Inostroza M; Matías Bahamondes F; Paloma Lillo U; Jaime Hinzpeter C (Journal of Sports and Exercise Medicine, 2019)
An anterior cruciate ligament (ACL) injury is an important cause of rest in athletes. In most cases, ACL injuries do not require external contact and they are associated with biomechanical risk factors that increase ACL tension. The increase of the hip flexion angle (HF) is included within these. The ACL requires cooperation of the periarticular musculature of the knee, muscle groups, hip stabilizers and CORE muscles; consequently, fatigue caused by exercise would alter the balance and put this ligament at risk. The objective of the study is to determine the angular behavior for HF before and after a physical load (a standardized training) in children between 11 and 12 years old. A non-randomized clinical study was carried out. The sample consisted of 50 soccer school students born between 11 and 12 years old. The angular behavior of HF was compared before and after performing a training session. The angular behavior was measured through the Drop Jump test (DJ), with data obtained by inertial sensors. After the exercise, there was a significant increase in HF. It was concluded that the angular behavior of HF increases significantly in both extremities after training and that preventive measures must be applied for neuromuscular control of the hip.
Keywords: Anterior Cruciate Ligament